Selection of Pseudomonas sp. for Lipid and Detergent Degradation - Nur Hidayat; Luqman Nur Chandra (APTA and DTIP FTP UGM, 2017)
The objective of the research was to identify which Pseudomonas species has the ability to alter lipids and surfactants simultaneously. This research was conducted by using three Pseudomonas species, vegetable oil, and commercial detergent which contains Linear Alkyl Sulfonate LAS. The result shows that Pseudomonas aeruginosa is able to reduce lipids and surfactant 80.53% and 61.22% respectively.